Decreasing pH impairs sexual reproduction in a Mediterranean coral transplanted at a CO2 vent. Issue 11 (25th September 2021) - Marchini, Chiara; Gizzi, Francesca; Pondrelli, Thomas; Moreddu, Lisa; Marisaldi, Luca; Montori, Francesco; Lazzari, Valentina; Airi, Valentina; Caroselli, Erik; Prada, Fiorella; Falini, Giuseppe; Dubinsky, Zvy; et al.
ABSTRACT: Ocean acidification, due to the increase of carbon dioxide (CO2 ) concentration in the atmosphere and its absorption by the oceans, affects many aspects of marine calcifying organisms' biology, including reproduction. Most of the available studies on low pH effects on coral reproduction have been conducted on tropical species under controlled conditions, while little information is reported for either tropical or temperate species in the field. This study describes the influence of decreasing pH on sexual reproduction of the temperate non‐zooxanthellate colonial scleractinian Astroides calycularis, transplanted in four sites along a natural pH gradient at the underwater volcanic crater of Panarea Island (Tyrrhenian Sea, Italy). The average pH values of each site (range: pHTS 8.07–7.40) match different scenarios of the Intergovernmental Panel on Climate Change (IPCC) for the end of the century. After 3 months under experimental conditions, the reproductive parameters of both oocytes and spermaries (abundance, gonadal index, and diameters) seem to be unaffected by low pH. However, a delay in spermary development in the pre‐fertilization period and a persistence of mature oocytes in the fertilization period were observed in the most acidic site. Furthermore, no embryos were found in colonies from the two most acidic sites, suggesting a delay or an interruption of the fertilization process due to acidified conditions. These findings suggest a negative effect of low pH on A. calycularis sexual reproduction. However, long‐term experiments, including the synergistic impact of pH and temperature, are needed to predict if this species will be able to adapt to climate change over the next century.